Duration of nursing care in patients with hip fractures - Harapin Savić, Tihana (Array, 2019)
The research regarding the duration of nursing care in patients with hip fractures was conducted at the Traumatology and Orthopedic Institute of the University Hospital Dubrava in a period of 4 months. The research was conducted on 59 patients with a diagnosis of a broken hip, that have undergone surgery. The goal of this research was to determine the differences in the duration of nursing care due to age, gender, comorbidities and postoperative day. Statistical significance in all measurements was reduced to p<0.05. The research shows connection between patient age and the duration of nursing care. The presence of comorbidity also prolongs the duration of nursing care. Shorter duration of nursing care was determined in women compared to men in all age groups, but it wasn’t of statistical significance.